Guardians of Health: Vaccines in the Battle Against Communicable Diseases Effective Communication Strategy with Vaccination Hesitancy - Ismail, Zulkifli; Balasundaram, Susheela; Megat Hashim, Megat Mohamad Amirul Amzar Bin (International Journal of Human and Health Sciences (IJHHS), 2025)
The COVID-19 pandemic has amplified the complexities of vaccine hesitancy, creating new challenges for healthcare providers (HCPs) in their efforts to maintain vaccination coverage. Addressing this issue requires more than just delivering information; it demands tailored communication strategies that engage patients respectfully and reduce stigmatization. This presentation aims to equip HCPs with effective approaches to vaccine communication, focusing on strategies that help prevent burnout and avoid the pitfalls of using non-specific, one-size-fits-all techniques. Drawing from a qualitative study of primary healthcare professionals in Malaysia, the need for adaptive communication approaches is evident. The study’s findings emphasize the diverse experiences and challenges faced by HCPs, including the impact of inconsistent messaging and the emotional toll of confronting fixed-minded vaccine refusers. These insights underscore the importance of developing a nuanced communication module that addresses the broad spectrum of vaccine hesitancy while promoting patient-centered engagement. The presentation will explore practical strategies for fostering open, empathetic dialogues using tools such as the OARS framework (Open-ended questions, Affirmation, Reflective listening, Summarizing) and the ESV approach (Elicit, Share, Verify). Emphasizing a presumptive approach can help normalize vaccine acceptance, while tailored strategies address specific concerns and build trust. By focusing on reducing stigmatization and employing flexible techniques, HCPs can improve the quality of vaccine discussions, reduce their risk of burnout, and support better vaccination outcomes in the evolving post-pandemic landscape. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S22